Deutschland, Russland, Komintern. II. Dokumente (1918–1943). Nach der Archivrevolution: Neuerschlossene Quellen zu der Geschichte der KPD und den deutsch-russischen Beziehungen - Albert, Gleb (Archive des Kommunismus - Pfade des XX. Jahrhunderts, 2014)
Since its creation in 1998, the “German-Russian Historical Commission” has conducted research on the Communist International. Thanks to the archival revolution, the Commission has succeeded in closing important gaps in earlier research on German–Russian relations and the history of German communism. This volume contains over 500 documents, and will become a standard work long consulted by future researchers